2017
DOI: 10.1101/226167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Functional Connectivity between the Locust Leg Pattern Generating Networks and the Subesophageal Ganglion Higher Motor Center

Abstract: 30Interactions among different neuronal circuits are essential for adaptable 31 coordinated behavior. Specifically, higher motor centers and central pattern generators 32 (CPGs) induce rhythmic leg movements that act in concert in the control of locomotion. 33Here we explored the relations between the subesophageal ganglion (SEG) and thoracic 34 leg CPGs in the desert locust. Backfill staining revealed about 300 SEG descending 35 interneurons (DINs) and some overlap with the arborization of DINs and leg motor … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 78 publications
2
4
0
Order By: Relevance
“…Here we have shown that inputs from the locust SEG modulate interactions between sensory inputs and motor output. Consistent with our previously suggested roles of the insect SEG in leg control (David et al 2016;Knebel et al 2017b), we have shown here that SEG descending signals facilitate intersegmental transfer of sensory information for a functional coordination.…”
Section: Fig 4 Specific Lesioning Experiments Reveal the Pathway Of Transferring The Sensory Signals (A)supporting
confidence: 92%
See 4 more Smart Citations
“…Here we have shown that inputs from the locust SEG modulate interactions between sensory inputs and motor output. Consistent with our previously suggested roles of the insect SEG in leg control (David et al 2016;Knebel et al 2017b), we have shown here that SEG descending signals facilitate intersegmental transfer of sensory information for a functional coordination.…”
Section: Fig 4 Specific Lesioning Experiments Reveal the Pathway Of Transferring The Sensory Signals (A)supporting
confidence: 92%
“…We have also recently reported that SEG DUM neurons receive an efference copy of the legs' motor output and deliver descending commands (Knebel et al 2017b). The long and highly variable response latencies to the different stimuli observed in the current study, with median delays of up to 480 ms, support the involvement of multi-synaptic 'sensory to neuromodulatory' pathways.…”
Section: Interactions Of Sensory Inputs and Higher Motor Centers In Walking Behaviorsupporting
confidence: 79%
See 3 more Smart Citations